Adaptasi Alat Ukur Workplace Incivility Scale - Nadilla, Meisya Putri; Afifah, Salma Fairuz; Putri, Sari Kusuma Dwi; Mukminin, Ghinaya Ummul; Wyandini, Diah Zaleha (JURNAL PSIKOLOGI INSIGHT, 2021)
AbstractIncivility is undeniable in modern organizations and almost in all industries (Hendryadi, 2018). Therefore, the researcher wants to adapt the Workplace Incivility Scale from Jimenez et al., (2018) measuring tool with a Cronbach's alpha reliability of 0,87. Adapted measuring instruments are given to employees or individuals who are currently working in West Java with an age range of 20- 60 years. The adjusted workplace incivility scale has a Cronbach Alpha reliability value of 0,937 and a Corrected-Item Total Correlation that exceeds 0.20 without removing the original item so that this measuring tool is feasible to use. The results of this study resulted in 6 factor extractions by adding 3 new dimensions, namely coworker impoliteness, impolite provocation, leader impoliteness, suspicion in the work environment, and distrust of leaders.AbstrakKetidaksopanan merupakan hal yang tidak bisa dipungkiri terjadi dalam organisasi modern dan hampir di semua industry (Hendryadi, 2018). Penelitian ini bertujuan untuk mengadaptasi alat ukur Workplace Incivility Scale dari Jimenez et al., (2018) dengan reliabilitas Cronbach’s alpha sebesar 0,87. Partisipan dengan rentang usia 20-60 tahun. Workplace incivility scale yang sudah diadaptasi memiliki nilai reliabilitas Cronbach Alpha sebesar 0,937 dan Corrected-Item Total Correlation yang melebihi 0,20 tanpa membuang item asli sehingga alat ukur ini layak untuk dipakai. Hasil penelitian ini menghasilkan 6 ekstraksi faktor dengan menambahkan tiga dimensi baru yakni ketidaksopanan rekan kerja, provokasi ketidaksopanan, ketidaksopanan pimpinan, kecurigaan di lingkungan kerja, lingkungan kerja, dan ketidakpercayaan pemimpin